Implementasi Metode Fun Learning Pada Pembelajaran Tematik untuk Meningkatkan Motivasi Belajar Siswa Kelas 2 Madrasah Ibtidaiyah - Kamto Kamto; Ulil Hidayati (AL-BURHAN, 2023)
Implementation of the fun learning Method in Thematic Learning to Increase Student Motivation in Class 2 at MI Hidayatul Islam Gembong. This study aims to find out how the implementation of the fun learning method in thematic learning to increase the learning motivation of Grade 2 students at MI Hidayatul Islam Gembong. The purpose of this research is theoretically to add to the body of knowledge regarding the Implementation of the fun learning Method in thematic learning, which can be used as literature in conducting relevant research in the future. This research can also add insight to teachers about the application of fun learning methods in thematic learning to increase student motivation. The approach in this research is qualitative, which is the method that must be followed in producing descriptive data, in the form of words (can be spoken for social, cultural, philosophical research), notes related to meaning, value and understanding. The characteristics of qualitative research are on the object that is the focus of the research. The type of research here uses field research. By seeing and getting down to the field directly, as well as observing the conditions that exist in MI Hidayatul Islam Gembong, which is a research that has the intention to express something systematically and accurately, where certain situations are factual. The conclusions from this study are (1) The fun learning method is used by the teacher to deliver thematic learning material in class 2 by taking one of the themes